Meningkatkan Pelayanan Kesehatan Ibu Dan Bayi Baru Lahir Melalui Kunjungan Neonatal - Rina Kusumaratna; Audrey Arnelia; Nadira Aqsenta; Woro Surya Annisa; Utami Wulandari (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Health efforts to reduce the risk of health problems in infants under one month old include three neonatal visits (KN1-KN3). These visits aim to increase neonatal access to basic health services and detect infant abnormalities early. Services, provided by doctors, midwives, or nurses, can be conducted at health centers or through home visits, involving infant examinations and counseling for mothers. Community service activities include refreshing cadres, home and partner visits, making reporting barcodes for partners and health promotion for mothers. The results showed significant relationships between mothers' knowledge (p = 0.018), beliefs (p = 0.003), and attitudes (p = 0.039) with the neonatal visits conducted. Continuous education for health cadres about the importance of complete neonatal visits is essential to achieve comprehensive service coverage for infants under one month old.